Analysis of the concept of nurses’ autonomy in intensive care units: A hybrid model - Taleghani, Fariba; Dehbozorgi, Raziye; Babashahi, Monire; Monemian, Sharife; Masoumi, Masoume (Investigación y Educación en Enfermería, 2023)
Objective. To analyze the concept of autonomy of nurses in Intensive Care Units (ICU). Methods. The hybrid model approach proposed by Schwartz-Barcott and Kim, which includes theoretical, fieldwork and analytical phases, was used for this study. For the theoretical and fieldwork phases, the Graneheim and Lundman stages and the CORE-Q checklist were used, and the results were combined in the final analysis phase. For the theoretical phase, 46 related articles, two instruments and four books were identified after using a search strategy in 7 bibliographic databases in English and one in Persian with the terms MESH: "nursing", "autonomy"; and "intensive care";. The information extracted in the theoretical phase served as the basis for the design of the questions used in the semi-structured interviews in the fieldwork phase. Eight nurses with ICU experience working in hospitals affiliated to Isfahan University of Medical Sciences (Iran) participated in the fieldwork phase. Results. The antecedents of the concept of nurse autonomy in ICUs were: empowerment of the workforce, organizational platform, and social and individual views of the profession. Its attributes were professionalism and high personal capabilities. Finally, increased personal competencies, promotion of quality of care, improved attitudes towards the profession and professional outcomes were noted as consequences. Conclusion. The autonomy of nurses in the ICU can facilitate their empowerment, which translates into the promotion of their caring behaviours, followed by the improvement of patient outcomes and quality of care.